Հովհան Դամասկացուն վերագրված «Յաղագս հռովմէացւոց» երկը - Մուրադյան, Գոհար (Մատենադարան)
The works of John of Damascus were translated into Armenian from Georgian in the 13th century by Simēon Pghndzahanets‘i. The manuscripts of the corpus often contain a sermon On the Romans. Eustratius of Nicaea (metropolitan bishop of Nicaea in the early 12th c., pupil of John Italus) is mentioned as its author. It is a criticism of the Latin Church from the point of view of the Greek Church. Труды Иоанна Дамаскина, переведенные на армянский с грузинского в 13ом веке Симеоном Пгндзаанеци, в рукописях сопровождает Слово о римлянах, причем в заглавии упоминается имя Евстратия Никейского (митрополита Никеи в нач. 12-го века, ученика Иоанна Итала). В нем содержится критика латинской церкви с точки зрения церкви греческой.
Keywords: Բանասիրություն